2002
DOI: 10.1002/jbm.10172
|View full text |Cite
|
Sign up to set email alerts
|

Initial interaction of U2OS cells with noncoated and calcium phosphate coated titanium substrates

Abstract: From previous studies, we know that calcium phosphate (CaP) coated implants stimulate bone formation compared to uncoated implants. Nevertheless, the mechanism by which substrate surface characteristics affect cell function is unclear. In this study, we examined the initial interaction (30 min to 24 h) of U2OS cells with titanium substrates with or without a CaP coating. The effect of substrate roughness was also studied. When cell attachment was studied, we found that cells attached more readily to rough than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
24
0
3

Year Published

2004
2004
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 60 publications
6
24
0
3
Order By: Relevance
“…In the present experiment, when analyzed by SEM, the cells were shown to have a large flattened body with short cellular prolongations, in agreement with what has been observed in the related literature with respect to cellular interaction and smooth surfaces 21 In contrast, cells on rough surfaces present a more elongated or polygonal shape, and longer cellular extensions. 25,26 We also observed that the cells analyzed followed a direction parallel to the machining scratches. The literature relates this tendency in machined implants as opposed to rough surfaces, where the cells proliferate over the entire surface without any predominant direction.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…In the present experiment, when analyzed by SEM, the cells were shown to have a large flattened body with short cellular prolongations, in agreement with what has been observed in the related literature with respect to cellular interaction and smooth surfaces 21 In contrast, cells on rough surfaces present a more elongated or polygonal shape, and longer cellular extensions. 25,26 We also observed that the cells analyzed followed a direction parallel to the machining scratches. The literature relates this tendency in machined implants as opposed to rough surfaces, where the cells proliferate over the entire surface without any predominant direction.…”
Section: Discussionmentioning
confidence: 70%
“…The cells on rough substrates present a more polygonal shape. 25,26 Some studies have shown that, in implants with machined surfaces, cells have a tendency to follow an orientation parallel to the scratches arising from the machining of the titanium surface (anisotropic characteristic) as opposed to rough surfaces, where the cells spread throughout the entire extent of the surface (isotropic characteristic). [27][28][29] In view of the foregoing explanations, the aim of the present in vitro study was to analyze the biocompatibility of an implant surface, observing the adhesion, cell morphology and proliferation of an osteoblastic cell lineage 30 cultivated on a commercially available dental implant (Titamax Liso  , Neodent, Curitiba, PR, Brazil) through scanning electron microscopy (SEM).…”
mentioning
confidence: 99%
“…With increasing gravity (50 g) this other pathway also becomes affected. Similar adaptive behaviour of integrin expression has also been described by others [ter Brugge et al, 2002]. The statistical analysis performed on the fluorescence micrographs revealed two turning points signifying that anchor proteins are up-or down-regulated at different g-forces.…”
Section: Discussionmentioning
confidence: 75%
“…Anselme's results [13] indicated that the cultured human osteoblasts "preferred" grooved Ti surfaces with a relatively high micro-roughness amplitude and a low level of repeatability. The initial cell-substrate interaction (30 min~24 h) revealed that U2OS cells attached more readily to rougher Ti surfaces than to smoother ones [14]. On the other hand, Ball, et al [15] concluded that cells on the ordered surfaces could spread or elongate fully, while the shape of cells on the rough surfaces was constrained to a great extent.…”
Section: Introductionmentioning
confidence: 99%